CS Unplugged or Coding Classes? Perhaps a more appropriate question is 'Why not both'? - Bell, Tim (Communications of the ACM, 2021)
The article criticizes the constructivist computer science education methodology known as "computer science unplugged". The author outlines the goals for computer science education for younger students, the alleged need for diversity in computer science education is outlined, and the author cautions against misconstruing "unplugged" as a computer programming curriculum rather than a pedagogy.